Pengaruh dari Rasio Utang Terhadap Ekuitas (DER), Rasio Lancar (CR) dan Pengembalian Aset (ROA) Pada Harga Saham PT. Indofood Sukses Makmur Tbk Rentang Waktu 2009-2023 - Manurung, Sarveli (Jurnal Sistem Informasi, Akuntansi dan Manajemen, 2024)
This study aims to analyze the effect of DER, CR, and ROA on the stock price of PT Indofood Sukses Makmur Tbk in the period 2009-2023. The research method used is multiple linear regression with secondary data in the form of company financial statements. The results showed that DER and CR had a significant effect on stock prices, while ROA had no significant effect. DER has a negative influence, which indicates that an increase in debt relative to equity tends to reduce stock prices. CR also has a negative influence, indicating that an increase in liquidity does not always go hand in hand with an increase in stock price. Meanwhile, ROA does not contribute significantly to stock price movements. These results are important for investors to consider financial ratios in making investment decisions.